2015
DOI: 10.1159/000435873
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Migration in Patients with Perimodiolar Cochlear Implant Electrodes

Abstract: Migration of a cochlear implant electrode is a hitherto uncommon complication. So far, array migration has only been observed in lateral wall electrodes. Between 1999 and 2014, a total of 27 patients received bilateral perimodiolar electrode arrays at our institution. The insertion depth angle was estimated on the initial postoperative scans and compared with the insertion depth angle of the postoperative scans performed after contralateral cochlear implantation. Seven (25.93%) patients were found to have an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Post-implantation migration is the second most common reason for revision cochlear implantation, emphasizing the clinical issues related to electrode migration ( Brown et al 2009 ; Connell et al 2008 ; Green et al 2004 ; Wang et al 2014 ). Prevalence of electrode migration varies from 7.4% to 29%, and seems to occur more frequently and to a greater extent in lateral-wall electrodes than perimodiolar electrodes ( Mittmann et al 2015 ; van der Marel et al 2012 ). It is suggested that these migrations mostly happen during perioperative conditions, for example, while closing the skin when minor manipulations of the implant might occur, or in the first few weeks postoperative when the electrode array is not yet immobilized by ossification or fibrous tissue ( van der Marel et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Post-implantation migration is the second most common reason for revision cochlear implantation, emphasizing the clinical issues related to electrode migration ( Brown et al 2009 ; Connell et al 2008 ; Green et al 2004 ; Wang et al 2014 ). Prevalence of electrode migration varies from 7.4% to 29%, and seems to occur more frequently and to a greater extent in lateral-wall electrodes than perimodiolar electrodes ( Mittmann et al 2015 ; van der Marel et al 2012 ). It is suggested that these migrations mostly happen during perioperative conditions, for example, while closing the skin when minor manipulations of the implant might occur, or in the first few weeks postoperative when the electrode array is not yet immobilized by ossification or fibrous tissue ( van der Marel et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The electrode array position was reconstructed and evaluated from the postoperative CT imaging made in the first 24 h. Previous studies showed that a migration (25) or an extrusion of the electrode array is a complication that could be suspect when a gradual increase of the impedances is observed (26). In our study, there was no assessed a slight migration of the electrode array, however a postoperative CT scan was performed in case of an unexplained degradation or a persistence of poor hearing performance.…”
Section: Discussionmentioning
confidence: 92%
“…In a study conducted by Mittman et al has described those fixation techniques like fixation clips can be thought to minimize the risk of electrode migration or misplacement [7]. In one study by Kubo et al described that electrode extrusion is although rare complication but it can lead to re implantation surgery and it may occur after a few years from surgery but fixation of the electrode into split made in the buttress part may prevent electrode migration [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, electrode migration or extrusion is an important complication in CI surgery, which affects the hearing level, and induce facial nerve stimulation, that may require a revision. Electrode migration is defined as a complication due to gradually slip out of electrodes from cochlea or extrusion from the tympanic membrane [7] due to raise the level of impedance values in basal side electrodes. As well as, it can be due to cochlear ossification (Figure 1) [8].…”
Section: Introductionmentioning
confidence: 99%